PENINGKATAN KUALITAS PRODUKSI PAKAIAN PADA USAHA KONVEKSI SUSILAWATI DENGAN BERBASIS METODE SIX SIGMA - Steven Teja; Ahmad Ahmad; Lithrone Laricha Salomon (Jurnal Ilmiah Teknik Industri, 2022)
Usaha Konveksi Susilawati is one of the businesses engaged in convection that produces t-shirts that still have problems with defective products in the form of messy stitches, asymmetrical seams, incomplete accessories, unclean t-shirts, and inaccuracies in size, so quality control is necessary with the six sigma method.. Research This aim is to improve the quality of cotton combed t-shirt production using the DMAIC stage. This research begins with making a project charter and collecting data. It was found that there were four data that were outside the control limits, so improvement was needed. After that, the data is continued by calculating the DPMO value is 8,1350.80 and converting it into a sigma level of 3.90. With this sigma level value, it can be said that this company is at a profit of 25-40% sales and only reaches 93.3% customer satisfaction level. The results of FMEA analysis with the highest RPN value are method factors because there is no clear SOP. At the improve stage using the 5W+1H method, Kaizen 5S theory and Poka Yoke. Based on the improvement plan, a proposal for improving the design of a new work SOP can be made. The control stage is carried out by re-testing the company's production data after implementing the proposed improvement. The results obtained are the DPMO value of 2,063.71 and converted to a sigma level of 4.37. This shows that the production quality of the Usaha Konveksi Susilawati’s clothing has increased after the implementation.